Plane Symmetric String Cosmological Model With Zero Mass Scalar Field In F(R) Gravity - Kalpana Pawar; Dabre, A. K.; Pallavi Makode (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In this article, an anisotropic Locally Rotationally Symmetric (LRS) Bianchi type I metric in the presence of cloud string fluid and zero mass scalar field in reference to f (R) gravity have been investigated. To obtain the deterministic solutions we assumed the weak field limit for a pointlike source f (R) = R3/2 and the very well-known expansion-shear scalar proportionality relation. Furthermore, some physical and kinematical parameters have been calculated to study the astrophysical consequences of obtained model, which shows a good resemblance to the recent observational data.
Keywords: Astrophysics